2020
DOI: 10.3389/fphar.2020.559607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Action of Emodin: As an Anti-Cardiovascular Disease Drug

Abstract: Emodin is a natural occurring anthraquinone derivative isolated from roots and barks of numerous plants, molds, and lichens. It is found to be an active ingredient in different Chinese herbs including Rheum palmatum and Polygonam multiflorum, and it is a pleiotropic molecule with diuretic, vasorelaxant, anti-bacterial, anti-viral, antiulcerogenic, anti-inflammatory, and anti-cancer effects. Moreover, emodin has also been shown to have a wide activity of anti-cardiovascular diseases. It is mainly involved in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 130 publications
(182 reference statements)
1
23
0
Order By: Relevance
“…Moreover, benznidazole emodin combinations may be tested for potential synergistic antichagasic effects in vivo. However, as reviewed recently, emodin shows relatively low oral bioavailability in rodents (5-10%) (Li et al, 2020). As some anthraquinones did not inhibit T. cruzi epimastigote proliferation in our study (Table 5), their antichagasic effects in the infection/parasite release assays may be due to host cell ROS generation induced by these compounds.…”
Section: Ll Open Access Isciencesupporting
confidence: 43%
“…Moreover, benznidazole emodin combinations may be tested for potential synergistic antichagasic effects in vivo. However, as reviewed recently, emodin shows relatively low oral bioavailability in rodents (5-10%) (Li et al, 2020). As some anthraquinones did not inhibit T. cruzi epimastigote proliferation in our study (Table 5), their antichagasic effects in the infection/parasite release assays may be due to host cell ROS generation induced by these compounds.…”
Section: Ll Open Access Isciencesupporting
confidence: 43%
“…Lipoxygenases (LOXs) are potential treatment targets in a variety of inflammatory conditions, enzyme kinetics showed that aloe emodin inhibited lipoxygenase competitively with an IC 50 of 29.49 μM [126]. Compound 215 was reported to possess wide biological activities including anti-inflammatory, neuroprotection, anti-cardiovascular and α-glucosidase inhibitory activity [129][130][131][132]. It exhibited potent inhibition of α-glucosidase with an IC 50 value of 19 ± 1 μM and lower cytotoxicity to the Caco-2 cell line [132].…”
Section: Emodinsmentioning
confidence: 99%
“…Anthraquinones are a class of aromatic compounds demonstrating a broad spectrum of bioactivities. Emodin (32) and aloe-emodin (33) are active ingredients in different Chinese herbs including Aloe vera, Cassia occidentalis, Rheum palmatum, and Polygonam multiflorumto and possesses broad pharmacological effects, such as antibacterial, antiviral, antiinflammatory, anticancer, neuroprotective, hepatoprotective, and anticardiovascular effects [134][135][136][137][138][139]176,177]. At a concentration of 50 µg/mL, 32 inhibited HSV-1 and 2 in Hep-2 cells with antiviral indices of 2.07 and 3.53, respectively, and the compound with equivalent antiviral efficacy to acyclovir also increased the survival rate and time of HSVinfected mice with higher efficacy in eliminating HSV-infected brain, heart, liver, and ganglion compared to the viral control [135].…”
Section: Anthraquinones and Anthracyclines With Potential Antiherpetic Activitiesmentioning
confidence: 99%